Role of staging laparoscopy in peri-pancreatic and hepatobiliary malignancy - Gaujoux, Sebastien (Baishideng Publishing Group Co., Limited, 2010)
Even after extensive preoperative assessment, staging laparoscopy may allow avoidance of non-therapeutic laparotomy in patients with radiographically occult metastatic or locally unresectable disease. Staging laparoscopy is associated with decreased postoperative pain, a shorter hospital stay and a higher likelihood of receiving systemic therapy compared to laparotomy but its yield has decreased with improvements in imaging techniques. Current uses of staging laparoscopy include the following: (1) In the staging of pancreatic adenocarcinoma, laparoscopic staging allows for the identification of sub-radiographic metastatic disease in locally advanced cancer in approximately 30% of patients and, in radiographically resectable cancer, may identify metastatic disease in 10%-15% of cases; (2) In colorectal liver metastases, selective use of laparoscopic staging in patients with a clinical risk score of over 2 identifies unresectable disease in approximately 20% of patients; (3) In hepatocellular carcinoma, laparoscopic staging could be selectively used in high-risk patients such as those with clinically apparent liver cirrhosis and in patients with major vascular invasion or bilobar tumors; and (4) In biliary tract malignancy, staging laparoscopy may be used in all patients with potentially resectable primary gallbladder cancer and in selected patients with T2/T3 hilar cholangiocarcinoma. Because of the decreasing yield of SL secondary to improvements in imaging techniques, staging laparoscopy should be used selectively for patients with pancreatic and hepatobiliary malignancy to avoid unnecessary non-therapeutic laparotomy and to improve resource utilization. Each individual surgeon should apply his or her threshold as to whether staging laparoscopy is indicated according to the quality of preoperative imaging studies and the availability of resources at their own institution.